CFTR transcription defects in pancreatic sufficient cystic fibrosis patients with only one mutation in the coding region of CFTR. Issue 4 (20th November 2010) - Sheridan, Molly B; Hefferon, Timothy W; Wang, Nulang; Merlo, Christian; Milla, Carlos; Borowitz, Drucy; Green, Eric D; Mogayzel, Peter J; Cutting, Garry R
Abstract : Background: Patients with cystic fibrosis (CF) manifest a multisystem disease due to deleterious mutations in each gene encoding the cystic fibrosis transmembrane conductance regulator ( CFTR ). However, the role of dysfunctional CFTR is uncertain in individuals with mild forms of CF (ie, pancreatic sufficiency) and mutation in only one CFTR gene. Methods: Eleven pancreatic sufficient (PS) CF patients with only one CFTR mutation identified after mutation screening (three patients), mutation scanning (four patients) or DNA sequencing (four patients) were studied. Bi-directional sequencing of the coding region of CFTR was performed in patients who had mutation screening or scanning. If a second CFTR mutation was not identified, CFTR mRNA transcripts from nasal epithelial cells were analysed to determine if any PS-CF patients harboured a second CFTR mutation that altered RNA expression. Results: Sequencing of the coding regions of CFTR identified a second deleterious mutation in five of the seven patients who previously had mutation screening or mutation scanning. Five of the remaining six patients with only one deleterious mutation identified in the coding region of one CFTR gene had a pathologic reduction in the amount of RNA transcribed from their other CFTR gene (8.4–16% of wild type). Conclusions: These results show that sequencing of the coding region of CFTR followed by analysis of CFTR transcription could be a useful diagnostic approach to confirm that patients with mild forms of CF harbour deleterious alterations in both CFTR genes.